Viewers’ choice: discrete choice elements of viewer’s in portal television usage and preferred types of programs watched frequency in achieving gratifications - Hashim, Norliana; Bolong, Jusang; Razak, Muhammad Nur Fitri (Human Resource Management Academic Research Society, 2021)
Changes in the Malaysian mass media landscape are on the rise and this has given the audience more choice to watch their favourite channels. Based on the theory of use and satisfaction, audiences are no longer considered passive. Audiences or viewers are now active and selective where the power to choose the media is in the hands of the audience itself. Adopting a uses and gratifications theory (UGT) perspective, the article aims to demonstrate the audience’s or viewer’s seeked satisfaction factors through watching the environment and intention portal TV mediated by its usage frequency and types of program. Drawing from viewing patterns and audience literature, relevant uses and gratifications for TV programs chosen were cognitive, emotional, personal, social, and self-expression. Discrete choice modeling (DCM) was adapted for the observed variables of predictors of the Partial Least Squares – Structural Equation Modeling (PLS – SEM) in this study. 500 respondents were participated in this study from Bandar Baru Bangi, Malaysia as the location. Cognitive and emotional needs are the most sought gratifications by the respondents when utilizing the portal TV. These two needs are influenced the discrete choice of elements of the viewers. Thus, this indicates that the Theory of Uses and Gratifications does highlighting the needs sought by the viewers.